(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, modern pedagogical approaches to the development of intercultural communication competence of foreign students of higher medical educational institutions, effective solutions to the problems of adaptation to the new cultural and social environment are highlighted on the basis of theoretical and practical data analysis.